Public Responsibilities Of Business Entities Under The Consumer Protection Laws - Wisnumurti, Rahadyan Widarsadhika; Putri, Dinda Silviana; Januari, Gregorius Eko (Journal Evidence Of Law, 2025)
This study seeks to examine the public accountability of business entities through the lens of consumer protection law, specifically addressing the types of legal liability that include criminal, civil, and administrative dimensions.  Consumer protection has emerged as a paramount concern due to the increasing intricacy of global trade, which poses numerous risks to consumers.  In this context, business entities are anticipated to behave responsibly concerning the products and/or services they provide in the marketplace.  The study utilises a normative legal methodology, incorporating statutory and conceptual frameworks.  The legal materials comprise primary sources, including statutory regulations, and secondary sources, such as legal literature and judicial rulings.  The results demonstrate that the responsibilities of business entities surpass contractual commitments and encompass ethical and societal obligations to guarantee the safety, comfort, and security of consumers.  Law No. 8 of 1999 on Consumer Protection explicitly mandates administrative, civil, and criminal penalties for infringements of consumer rights.  Consequently, the amalgamation of regulatory mechanisms, robust legal enforcement, and corporate ethical standards is crucial for the establishment of an equitable and sustainable consumer protection framework.